Statistical Data Analysis in Emergency Management Elements of Indian State of Tamil Nadu Manufacturing Industries Utilising LPG - Gnanasekara Baburao; Anitha Arivarasu; T. Srinivas; R. K. Elangovan; Rajendran Govindarajan (International Journal of Occupational Safety and Health, 2024)
Introduction: Process safety is becoming more difficult as requirements increase. When balancing quality, volume, and safety on a budget, major accidents are unavoidable. The inability of organizations to absorb unwelcome and unanticipated disruptions is a major contributor to complacency and a decline in safety attitudes. The inability of industries to interpret standards impedes self-regulation.